Mediación didáctica-pedagógica de la metodología STEM; una propuesta para el desarrollo de habilidades sociales (2022)
The assurance of learning entails the development of individual and collective capacities that are based on interdisciplinary perspectives from the converging contributions of different areas of knowledge. In this referential field, the present work aims to design a proposal for integrating the STEM methodology (Science, Technology, Engineering and Mathematics) into the curriculum as a basis for the development of Social Skills in primary school students. The study is based on a rationalist-deductive approach, mixed paradigm (multi-method) based on the complementarity between a qualitative and a quantitative component. The research is contextualized in the Simón Bolívar Tourist Technical Educational Institution of Puerto Colombia, Atlántico, Colombia, through three research stages: One of a theoretical nature where documents such as the guide for the institutional improvement of the self-assessment to the improvement plan (GUIDE 34) and the Institutional Educational Project (PEI) of the aforementioned institution; another of an empirical nature applying field design to observational units such as students, teachers, teaching directors and psycho counselors; Likewise, a proactive stage is addressed. The findings allow evidence regarding the disciplinary contents and the conception of the evaluation, which have been developed in a traditional way, therefore, to the extent that teachers plan strategies with active methodologies, students will be able to conceive the didactic cycle as an innovative and entertaining action.